A four parameter hardening model for TWIP and TRIP steels. (September 2020) - Lloyd, J.T.; Field, D.M.; Limmer, K.R.
Abstract: The mechanical behavior of twinning- and transformation-induced plasticity steels, commonly referred to as TWIP and TRIP steels, are characterized by linear hardening followed by an abrupt decrease in the hardening rate. We develop an empirical model that captures salient features of the strain hardening behavior. The model emphasizes ease of implementation into computer codes and identifying parameters from macroscopic data over physically motivated parameters; however, parameters fit to the mechanical response of several alloys show a direct correlation between some parameters and stacking fault energy. Finite element simulations of TWIP and TRIP steels under uniaxial tension show the lack of post-necking elongation observed experimentally is directly related to how abruptly the hardening decreases after the linear hardening regime. A scheme is then proposed for computing some hardening parameters directly from composition so that the model is compositionally-sensitive. This method is demonstrated on medium to high Mn steels so that the mechanical behavior can be predicted using the stacking fault energy, which is computed as a function of composition. Graphical abstract: Unlabelled Image Highlights: We develop a simple, robust strength model that appears to fit the mechanical behavior of TWIP and TRIP steels. The model predicts rapid failure in TWIP and TRIP steels is due to the rate of decrease in hardening rate. We show how the parameters of this model can be computed based on the stacking fault energy. We demonstrate that the model and method can be used to compute mechanical behavior of medium Mn steels from composition.